2007
DOI: 10.1590/s0102-311x2007001000006
|View full text |Cite
|
Sign up to set email alerts
|

Pessoas vivendo com HIV/AIDS: variáveis associadas à adesão ao tratamento anti-retroviral

Abstract: O estudo objetivou descrever o comportamento de adesão ao tratamento anti-retroviral em pessoas vivendo com HIV/AIDS e investigar preditores da adesão entre as variáveis escolaridade, presença de efeitos colaterais, interrupção anterior da terapia anti-retroviral (TARV) por conta própria, auto-estima, expectativa de auto-eficácia, estratégias de enfrentamento, suporte social e satisfação com a relação profissional de saúde-usuário. Adesão foi medida pelo auto-relato da perda do número de comprimidos/cápsulas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
57

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 21 publications
2
31
1
57
Order By: Relevance
“…This finding differs from those obtained by Saldanha, Andrade, and Beck 15 , who found a high rate of treatment adherence (72%), and by Seidl et al 16 , where the compliance rate reached 72.3%. However, in these studies with high drug compliance, there was a pharmacist intervention, which, when the present study was performed, was not available at the participating health centers.…”
Section: Discussioncontrasting
confidence: 85%
“…This finding differs from those obtained by Saldanha, Andrade, and Beck 15 , who found a high rate of treatment adherence (72%), and by Seidl et al 16 , where the compliance rate reached 72.3%. However, in these studies with high drug compliance, there was a pharmacist intervention, which, when the present study was performed, was not available at the participating health centers.…”
Section: Discussioncontrasting
confidence: 85%
“…A não adesão aos novos medicamentos antirretrovirais pode ser considerada uma ameaça tanto à efetividade do tratamento como para a disseminação de vírus-resistên-cia. Portanto, identificar os fatores que limitam a adesão é de grande relevância para que medidas que melhorem a adesão possam ser implementadas pela equipe de saúde [4][5][6] .…”
Section: Revisão De Literaturaunclassified
“…Despite the adverse effects immanent to ARV medications, children are aware of their need, and face their adverse effects in a paradoxical movement of rejection/acceptance. The adverse effects may mean a barrier, because taking medication can trigger unpleasant symptoms such as nausea, dizziness, malaise, added to the difficulties of communication between patients, and health professionals (15) . However, it is observed that children face adversity and claim to know and value the importance of continuing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is observed that children face adversity and claim to know and value the importance of continuing treatment. Even with the difficulties of adherence during the treatment, partly due to the complexity of ART, some medications must be taken on fast, or with some food, which requires a therapeutic plan developed from a restructuring and patient involvement in their treatment (15) . Thus, we highlight how complex it is to implement the ART to patients in general, which widens when it comes to children in a sensitive stage of growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation